Agricultural research - Poulton, Colin (International Food Policy Research Institute, 2009)
Although the majority of the material, including the case studies, in this volume focuses on institutional arrangements for either market development or natural resource management, the provision of relevant public goods (transport and communications infrastructure, irrigation investment, and agricultural research and investment) is also a key challenge for agricultural development policy in Africa. In this chapter I consider the challenge of improving the performance of agricultural research systems in Africa from an institutional perspective as an important example of the types of issues that arise in public good investments.